Analisis Manajemen Risiko pada UMKM Kerajinan Anyaman Family Handicraft Menggunakan Pendekatan ISO 31000 - Maisya Hayina Zahra; Ghina Aulia Asy-syifa; Nilam Meylani; Rahma Khairunnisa Amalia; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Micro, small, and medium enterprises (MSMEs) play a vital role in supporting local economic growth. Family Handicraft is one such MSME that produces handmade products using natural materials such as mendong and pandan. In its operations, this business faces various risks, ranging from uncertainty of raw materials, limited capital, to increasing market competition. This study uses an ISO 31000-based risk management approach to identify, assess, and analyze emerging risks and formulate appropriate mitigation strategies. Through observation, interviews, and documentation, a descriptive qualitative research methodology was used. To determine the business's strengths, weaknesses, opportunities, and threats, a SWOT analysis was added to the ISO 31000-based risk identification and evaluation phase. The study findings indicated that production and finance pose the greatest risks, including dependence on seasonal raw materials, revenue volatility, and inadequate digital promotion. These findings also show that Family Handicraft has the potential for development through the utilization of environmentally friendly product trends and increased digital marketing.